Externally Applied Static Magnetic Field Enhances Cardiac Retention and Functional Benefit of Magnetically Iron‐Labeled Adipose‐Derived Stem Cells in Infarcted Hearts. (8th July 2016) - Wang, Jian; Xiang, Bo; Deng, Jixian; Lin, Hung-Yu; Zheng, Dayang; Freed, Darren H.; Arora, Rakesh C.; Tian, Ganghong
Abstract : Although adipose‐derived stem cells (ASCs) hold the promise of effective therapy for myocardial infarction, low cardiac retention of implanted ASCs has hindered their therapeutic efficiency. We investigated whether an externally applied static magnetic field (SMF) enhances cardiac localization of "magnetic" cells and promotes heart function recovery when ASCs are preloaded with superparamagnetic iron oxide (SPIO) nanoparticles. The influence of SMF (0.1 Tesla) on the biological activities of SPIO‐labeled ASCs (SPIO ASCs) was investigated first. Fifty‐six female rats with myocardial infarction underwent intramyocardial injection of cell culture medium (CCM) or maleSPIO ASCs with or without the subcutaneous implantable magnet (CCM‐magnet orSPIO ASC‐magnet). Four weeks later, endothelial differentiation, angiogenic cytokine secretion, angiogenesis, cardiomyocyte apoptosis, cell retention, and cardiac performance were examined. The 0.1‐Tsela SMF did not adversely affect the viability, proliferation, angiogenic cytokine secretion, and DNA integrity ofSPIO ASCs. The implantedSPIO ASCs could differentiate into endothelial cell, incorporate into newly formed vessels, and secrete multiple angiogenic cytokines. Four weeks after cell transplantation, the number of cardiacSPIO ASCs was significantly increased, vascular density was markedly enlarged, fewer apoptotic cardiomyocytes were present, and heart contractile function was substantially improved in theSPIO ASC‐magnet treated rats in comparison with theSPIO ASC‐treated rats. TheSPIO ASCs could differentiate into endothelial cells, incorporate into vessels, promote angiogenesis, and inhibit ischemic cardiomyocyte apoptosis. An externally applied SMF offered a secure environment for biological properties ofSPIO ASCs, increased the cardiac retention of implanted magneticSPIO ASCs, and further enhanced heart function recovery after myocardial infarction. Significance: This pilot proof‐of‐concept study suggests that a 0.1‐Tesla static magnetic field does not adversely affect the viability, proliferation, angiogenic cytokine secretion, or DNA integrity of the superparamagnetic iron oxide‐labeled adipose‐derived stem cells (SPIO ASCs). Implantation of adipose‐derived stem cells promotes myocardial neovascularization and inhibits ischemic cardiomyocyte apoptosis through endothelial differentiation, incorporation into vessels, and paracrine factor secretion. An externally applied static magnetic field enhanced myocardial retention of intramyocardially injected "magnetic"SPIO ASCs and promoted cardiac function recovery after myocardial infarction. With further preclinical optimization, this approach may improve the outcome of current stem cell therapy for ischemic myocardial infarction. Abstract : Although adipose‐derived stem cells (ASCs) hold the promise of effective therapy for myocardial infarction (MI), low cardiac retention of implanted ASCs has hindered their therapeutic efficiency. We investigated whether an externally applied static magnetic field (SMF) enhanced cardiac localization of "magnetic" ASCs preloaded with superparamagnetic iron oxide (SPIO) nanoparticles and further improved heart function recovery. In conclusion, the SMF increased the cardiac retention of implanted "magnetic" SPIO‐labeled ASCs and enhanced heart function recovery after MI.